Por una Vida Digna: Science as Technique of Power and Mode of Resistance in Argentina (Alternautas, 2022)
Two decades after the approval of the use of GMO seeds in Argentina, the devastating consequences of the use of agro-chemicals linked to genetically modified seeds are becoming painfully clear. Rural populations are increasingly becoming aware of the dreadful environmental and health impacts of the use of the ‘technological package’ that has fuelled the expansion of Argentina’s agribusiness. Importantly, this paper provides an insight into how this growing awareness has become translated into greater community organisation across the country, with the aim of not only questioning the implementation of the current agribusiness model, but also the different ways in which these practices are legitimised. Her analysis of the movement for a Ciencia Digna (‘a dignified science’) demonstrates the epistemological battles that are fought in the everyday resistance organised by these communities.